Elevated IL-19 Serum Levels in Patients With Pernicious Anemia and Autoimmune Gastritis - Della Bella, Chiara; Antico, Antonio; Panozzo, Maria Piera; Capitani, Nagaja; Benagiano, Marisa; Petrone, Luisa; Azzurri, Annalisa; Pratesi, Sara; D’Elios, Sofia; Cianchi, Fabio; Ortiz-Princz, Diana; Bizzaro, Nicola; et al. (Frontiers in Immunology, 2022)
Pernicious anemia (PA) is a megaloblastic anemia consisting of hematological, gastric and immunological alterations. The immunopathogenesis of PA is sustained by both autoantibodies (e.g. intrinsic factor (IFA) antibodies and anti parietal cell (PCA) antibodies and autoreactive T cells specific for IFA and the parietal cell proton pump ATPase. Iron deficient anemia (IDA) is a microcytic anemia and represents the most common cause of anemia worldwide. Our work aimed to investigate serum levels of several interleukins (IL) of the IL-20 cytokine subfamily in patients with PA, with IDA and in healthy subjects (HC). We compared serum levels of IL-19, IL-20, IL-26, IL-28A and IL-29 in 43 patients with PA and autoimmune gastritis, in 20 patients with IDA and no autoimmune gastritis, and in 47 HC. Furthermore, we analyzed the IL-19 cytokine production by gastric lamina propria mononuclear cells (LPMC) in eight patients with PA and four HC. We found that patients with PA have significantly higher serum levels of IL-19 (163.68 ± 75.96 pg/ml) than patients with IDA (35.49 ± 40.97 pg/ml; p<0.001) and healthy subjects (55.68 ± 36.75 pg/ml; p<0.001). Gastric LPMC from all PA patients were able to produce significantly higher levels of IL-19 (420.67 ± 68.14 pg/ml) than HC (53.69 ± 10.92 pg/ml) (p<0.01). Altogether, our results indicate that IL-19 serum levels are significantly increased in patients with PA but not with IDA and that IL-19 is produced in vivo in the stomach of PA patients. These data open a new perspective on PA pathogenesis and suggest that IL-19 may represent a novel important tool for the management of patients with PA.